2008
DOI: 10.1111/j.1551-2916.2008.02299.x
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanofiber and Nanoparticle Synthesized Through Electrospinning and Their Photocatalytic Activity Under Visible Light

Abstract: In this paper, we fabricate ZnO nanofibers and nanoparticles through electrospinning precursor solution zinc acetate(ZnAc)/cellulose acetate(CA) in mixed‐solvent N,N‐dimethylformamide/acetone. Depending on the posttreatment of precursor ZnAc/CA composite nanofibers, both ZnO nanofibers and nanoparticles were synthesized after calcination of precursor nanofibers. The morphology and crystal structure of the ZnO nanofiber and nanoparticle were characterized by scanning electron microscopy, transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
60
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 22 publications
0
60
0
1
Order By: Relevance
“…25,26 Note that the controllability of the defect density depends on the type of defect and the semiconductor itself. 1,6,[8][9][10][11][12][13] In the context of ZnO, numerous studies deal with V O s, 4,8,10,11,13,21 which is not the case with Zn i s. It is also notable that the balance between the relative densities of Zn i s and V O s is still challenging. 15 The presence of Zn i s and V O s in ZnO can be easily identied by simple photoluminescence (PL) experiments, [15][16][17]27 indicated by blue and green emissions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Note that the controllability of the defect density depends on the type of defect and the semiconductor itself. 1,6,[8][9][10][11][12][13] In the context of ZnO, numerous studies deal with V O s, 4,8,10,11,13,21 which is not the case with Zn i s. It is also notable that the balance between the relative densities of Zn i s and V O s is still challenging. 15 The presence of Zn i s and V O s in ZnO can be easily identied by simple photoluminescence (PL) experiments, [15][16][17]27 indicated by blue and green emissions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,[28][29][30][31][32] In contrast, typically synthesized ZnO is predominant with V O s. 4,8,16,17,27,31,32 Consequently, photocatalysis studies involving V O s dominate the literature. 1,4,6,[8][9][10]13,21 In this context, it is very useful and important to study the effect of Zn i s in PCA and their efficiency against V O s. In addition to the fundamental interest, the results of such a study enable an efficient and cost effective design of novel photocatalysts. As shown earlier, 33 Zn i s are very unstable when compared to V O s, which are found to be stable even at 400 C. Aer nearly two years, theoretical support for this instability was provided by Janotti et al, 34 where the authors suggest that Zn i s diffuse faster through a migration barrier as low as 0.57 eV, cf.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ZnO nanoparticles and nanofibers have shown excellent photocatalytic properties because of their very high surface area and more porous nature. 48 Nevertheless, the metal oxide nanofibers are quite brittle and do not show any structural flexibility, and this cause significant problems during their handling and usage as a membrane material. For this reason, the development of flexible nanofibrous membranes or textiles having photocatalytic properties is still on demand for self-cleaning and water purification and waste treatment.…”
mentioning
confidence: 99%
“…48−53 Fibrous membranes made of nanofibers show remarkable photocatalytic properties due to their unique morphological features including high surface area and nanoporosity. 48,49,52,53 ZnO is an important semiconductor material with a direct wide band gap (3.37 eV) and it is a wellknown nontoxic catalyst and therefore, the potential application of ZnO for water purification has been investigated. 48,49,51 Because the morphology of ZnO is quite crucial for photocatalytic efficiency, ZnO nanostructures in the form of nanoparticles and nanofibers have been examined in terms of their photocatalytic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation